The Identity of Croats and the Croatian State in the Speeches and Messages of Pope John Paul II - Skoko, Božo (Poznańskie Studia Slawistyczne, 2016)
Starting from the concept of “external branding” of states and nations, the paper analyses the speeches and messages of Pope John Paul II dedicated to Croats and the Croatian state, spoken and published during his pontificate (1978–2005), in order to uncover how he perceived and presented the Croatian identity. The author believes that Pope John Paul II, thanks to his charisma and significant public impact, as well as extensive knowledge of the Croatian identity, contributed greatly to strengthening the recognisability of Croats in the global public and to promote their values, interests and aspirations.